Additives as a Support Structure for Specific Biochemical Activity Boosts in Anaerobic Digestion: A Review - Paritosh, Kunwar; Yadav, Monika; Chawade, Aakash; Sahoo, Dinabandhu; Kesharwani, Nupur; Pareek, Nidhi; Vivekanand, Vivekanand (Frontiers in Energy Research, 2020)
Anaerobic digestion is an attractive technology for resource management of organic waste and stubble. State of biochemical reactions and activities in anaerobic digestion determines the process stability. Biochemical activities such as syntrophic, metabolic, catalytic and enzymatic activities regulate the anaerobic efficiency for improved methane yield. Inhibitors such as accesses volatile fatty acids, ammonia, sulphur and heavy metals may slow down the anaerobic digestion and may cause reactor failure. However, additives for various biochemical activities may help to diminish the effect of inhibitors as well as improving process stability for enhanced methane yield. This manuscript presents an overview of various additives for enhancing the biochemical activities. The overview consists application of (a) conductive material for improving syntrophic activity, (b) trace metals for metabolic activities, (c) nanoparticles for improving catalytic activity, metabolism and symbiosis during AD, (d) biological additives for enzymatic action and (e) application of zeolite for introducing cation exchange property in anaerobic digestion. Also, comparison of various additives as per biochemical activity has also been performed for a deeper insight of application of additives in anaerobic digestion.